2013
DOI: 10.1371/journal.pone.0054376
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Extremely Low-Frequency Electromagnetic Fields Modulates Na+ Currents in Rat Cerebellar Granule Cells through Increase of AA/PGE2 and EP Receptor-Mediated cAMP/PKA Pathway

Abstract: Although the modulation of Ca2+ channel activity by extremely low-frequency electromagnetic fields (ELF-EMF) has been studied previously, few reports have addressed the effects of such fields on the activity of voltage-activated Na+ channels (Nav). Here, we investigated the effects of ELF-EMF on Nav activity in rat cerebellar granule cells (GCs). Our results reveal that exposing cerebellar GCs to ELF-EMF for 10–60 min significantly increased Nav currents (I Na) by 30–125% in a time- and intensity-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 47 publications
4
54
0
Order By: Relevance
“…in this study. Similar to our previous report , when cerebellar GCs were exposed to 1 mT ELF‐EMF for 60 min., the amplitude of the I Na increased by ~62.5 ± 6.6% ( n = 25, P < 0.05) compared with cells that were not exposed to ELF‐EMF ( n = 33, Fig. A).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…in this study. Similar to our previous report , when cerebellar GCs were exposed to 1 mT ELF‐EMF for 60 min., the amplitude of the I Na increased by ~62.5 ± 6.6% ( n = 25, P < 0.05) compared with cells that were not exposed to ELF‐EMF ( n = 33, Fig. A).…”
Section: Resultssupporting
confidence: 89%
“…An I Na was elicited by a depolarization step to −20 mV from the holding potential of −100 mV. Our previous study demonstrated that the increase in I Na amplitude induced by ELF‐EMF exposure was time dependent, and when cerebellar GCs were exposed to 1 mT ELF‐EMF for 60 min., the amplitude of the I Na increased significantly and was stable . Moreover, exposure cell or neuron to 1–5 mT EMF with short time was reported by Bai and Moghadam's studies .…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…This effect was detected also in adherent cells, as exposure at 50 Hz and 0.4 mT for 5 min induced clustering of epidermal growth factor receptors and activation of Ras GTPases in Chinese hamster lung (CHL) fibroblasts [21]. Other signaling pathways that are activated by short-term ELF-MF include cyclic AMP/protein kinase A (cAMP/PKA) in human skin fibroblasts exposed to 20 Hz and 7 -8 mT radiation for 60 min [22], as well as in rat cerebellar granule cells exposed to 60 Hz and 1 mT for 10 -90 min [23]. Another important signaling mechanism that appears to be influenced by ELF-MF is the elevation of intracellular Ca 2+ in exposed cells [24,25] within 1 min of exposure to ELF-MF at 50 Hz and 0.1 mT.…”
Section: Introductionmentioning
confidence: 99%
“…In the present of SC19220, PGE 2 only increased pPKC levels by 12.0 ± 7.8% ( n = 5, p >0.05 compared with control). To further verify that only EP1 was responsible for the intracellular effects of PGE 2 , we administered either an EP2 or EP4 receptor antagonist, AH6809 or AH23848, at concentrations that we have previously demonstrated to be effective [25,32]. Either antagonist was unable to eliminate the effects of PGE 2 on pPKC levels (Fig.…”
Section: Resultsmentioning
confidence: 99%